2013
DOI: 10.1371/journal.pone.0059426
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Cerebral Networks in Resting State with Sexual Preference of Homosexual Men: A Study of Regional Homogeneity and Functional Connectivity

Abstract: Recent imaging studies have shown that brain morphology and neural activity during sexual arousal differ between homosexual and heterosexual men. However, functional differences in neural networks at the resting state is unknown. The study is to characterize the association of homosexual preference with measures of regional homogeneity and functional connectivity in the resting state. Participants were 26 healthy homosexual men and 26 age-matched healthy heterosexual men in whom we collected echo planar magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Recently, behavioral and neuroimaging results from Perry et al (2013) showed empathy to be related to gender, as well as sexual preference. Further, a study aiming to characterize regional homogeneity and functional connectivity during rest found significant differences between homo- and heterosexual men (Hu et al, 2013). Hence, it would be presumptuous not to consider the ability to use this variable as a modulating factor to achieve homogeneous subject groups.…”
Section: Neuronal Correlates Of Andmentioning
confidence: 99%
“…Recently, behavioral and neuroimaging results from Perry et al (2013) showed empathy to be related to gender, as well as sexual preference. Further, a study aiming to characterize regional homogeneity and functional connectivity during rest found significant differences between homo- and heterosexual men (Hu et al, 2013). Hence, it would be presumptuous not to consider the ability to use this variable as a modulating factor to achieve homogeneous subject groups.…”
Section: Neuronal Correlates Of Andmentioning
confidence: 99%
“…While congruently suggesting a less pronounced or even sex‐reversed differentiation of cerebral midline structures, most previous studies were limited to a specific cerebral area (exceptions are Hu et al, , Abe et al, 2014) and a single metric; moreover, several of the studies only included male controls. Consequently, important facets of the possible neurobiology of sexual orientation remain unrevealed.…”
Section: Introductionmentioning
confidence: 98%
“…Zhou et al subsequently also found that smelling a putative male pheromone enhanced the visual perception of male figures among HoM and HeF, but not among HeM, indicating that hypothalamic activation in HoM and HeF had downstream effects on visual perception, potentially impacting sexual partner selection (Berglund, Lindstrom, Dhejne‐Helmy, & Savic, ; Berglund, Lindstrom, & Savic, ; Zhou et al, ). More recently, Hu et al () used MRI to measure homogeneity in resting‐state brain activity (presumably reflecting local functional connections), and found that HoM had greater homogeneity in the mid frontal lobe and lesser homogeneity in the middle and inferior occipital lobe compared to HeM.…”
Section: Introductionmentioning
confidence: 99%
“…These differences in the fALFF and FC suggest male sexual preference may influence the pattern of activity in the DMN. Although our previous study had shown differences between heterosexual and homosexual men in the ReHo and FC [13], the present study focused on the fALFF, which is a notably different analytical approach. Additionally, we should emphasize that the seeds and results of the FC analysis in the present study differed entirely from our previous investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Using the left inferior occipital gyrus as the seeding area, homosexual men showed decreased FC in the left middle temporal gyrus, left supra‐marginal gyrus, left inferior occipital gyrus, and right cuneus. Additionally, FCs in the right thalamus and right cuneus correlated positively with a homosexual preference [13].…”
Section: Introductionmentioning
confidence: 91%